THE PORTRAYAL OF THE ARTHUR’S CHARACTERIZATION, IMPICIT MEANING , AND MORAL VALUE FOUND IN JOKER MOVIE (2019) - Yuliana, Riska (Journal of English Education and Enterpreneurship (JEEP), 2021)
Characterization is an important part of building a story. Implicit meanings and moral values ​​are also intrinsic elements in the movie, just like characterizations. This research analyzes The Portrayal Of The Arthur’s Character, Implicit Meaning and Moral Value Found In Joker Movie (2019). The aim of this researh is to explore the portrayal of Arthur character, to describe the implicit meaning and find out the moral value. The object of this research is Arthur’s character, implicit meaning and moral value. Joker (2019) is the subject of this research. Descriptive qualitative is a method of this research.The result of this research showed that 8 Arthur’s characters using Boggs theory,15 implicit meanings and based on Linda and Eyrc theory the researcher found 9 moral values. Moral value can be divided into two groups as follow: value of being, which include values of being arehonesty, courage, peace ability, self - reliance and potential, self discipline and moderation, and also fidelity and chastity. Then value of giving, which include values of giving are: loyalty and dependability, respect, love, unselfishness and sensitivity, kindness and friendliness, and also justice and mercy.